AN INVESTIGATION OF FAILURE SOLVING ILL-STRUCTURED PROBLEMS: A CASE STUDY - Ninik Mutianingsih; Lydia Lia Prayitno; Eko Sugandi; Sri Rahmawati Fitriatien; Agus Prasetyo Kurniawan (IAIN Ambon, 2020)
63 students were involved in the study and elected Rizka as the subject of research. This is a case study aimed at describing the cause of Rizka's failure in solving ill-structured problems about the rectangle. The results showed that the subject was able to represent the problem with own language. Rizka failed to build a solution that corresponds to the problem due to partial mastery of the rectangular concept. Rizka uses trial and error because it fails to associate a problem with a square concept that is the key to problem-solving success. Rizka success in the justification process because the process is counting without giving meaning. Meanwhile, the monitoring and evaluation process carried out by Rizka has failed. Rizka confusion determines the final solution because the solution is built does not qualify the problem solution. This is where the Rizka fails to provide the final solution. In this case, teachers have a role to teach their students to build relationships between concepts that can be utilized in problem-solving.